Income and education as a source of health inequality. New UE countries case - Ucieklak-Jeż, Paulina (Research Papers of Wrocław University of Economics, 2018)
The objective of the research was testing the effect of the level of concentration of health needs in the countries of the, so called, New European Union in terms of income and education on the level of health inequality.When planning the study, the following research hypothesis was put forward: H1: there is a relation between meeting the self-reported health needs and the level of education or income of populations of New UE countries. The formulated hypothesis was explicitly confirmed during the analysis of the concentration of the three traits of health care accessibility, which showed that the highest level of concentration indicating a conscious need for taking advantage of specialist medical examinations necessary for the improvement of health was observed in social groups with high education (ED5_8) and income (Q80_100), Q60_80)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 181-192
Keywords: concentration; Herfindahl-Hirschman index; health concentration index; selfreported unmet needs; health needs; koncentracja; wskaźnik Herfindahla-Hirschmana; współczynnik koncentracji zdrowia; zgłaszanie niezaspokojonych potrzeb; potrzeby zdrowotne